Teologi Agraria: Rekonstruksi Konsep - Tantan Hermansah (Refleksi: Jurnal Kajian Agama dan Filsafat, 2007)
This writing seeks to reconstruct the concept of theology of the land (agrarian theology). It is a perspective that the issue of unequal access to agrarian resources is not only a socio-economic issue but also related to religious issues, especially the interpretation of a doctrine by key religious figures. In other words, the inequality of access to agrarian resources becomes more entrenched due to the legitimacy that claims the ‘good’ values of religion presented by these religious leaders. Therefore, Agrarian Theology aspires to become an instrument to break the stagnation that has long been dominated by both the ‘religious rulers’ and the excessive rulers of agrarian resources, resulting in endless poverty. Thus, the ‘stagnation’—if this term may be used—of the agrarian movement that has mostly operated at the socio-economic-political level can become more solid and have new ammunition. In this context, agrarian struggles are not only a social issue but also a struggle to uphold religious values.